Pharmacists's knowledge, attitude, and practices towards pharmaceutical and patient-centred care in asthma management: A national study - Dilan Çakmak; Muhammed Yunus Bektay; Anmar Al‑Taie; Saad Ahmed Ali Jadoo; Fikret Vehbi Izzettin (Elsevier, 2024)
Background: Asthma, a chronic respiratory disease, is effectively managed with medications, yet many patients struggle due to irregular treatment and poor adherence. Pharmacists play a crucial role in improving asthma care through pharmaceutical care (PC) services. This study aims to assess pharmacists' knowledge, attitudes, and behaviors regarding asthma PC in Türkiye. Methods: This cross-sectional study in Türkiye evaluated community (CP) and hospital pharmacists' (HP) knowledge level, attitudes, and behaviors regarding asthma care. A validated Asthma Pharmaceutical Care Knowledge (APCL) and Asthma Attitudes and Behaviors (AAB) questionnaires were used to assess their knowledge levels and attitudes toward asthma pharmaceutical care. Results: Out of 400 pharmacists participated the questionnaire, the majority were CP (297, 74.25 %). Both CP and HP demonstrated adequate knowledge scores, 79.39 ± 12.32 and 80.66 ± 12.25, respectively. APCL mean scores of CP and HP were 4.22 ± 0.523 and 4.29 ± 0.383. No statistically significant difference in asthma knowledge levels was observed between CP and HP. Both groups reported positive attitudes and behaviors toward asthma care, with CP scoring 4.71 ± 0.446 and HP scoring 4.74 ± 0.330 on the AAB questionnaire. Conclusions: This study revealed that both CP and HP have sufficient knowledge about asthma and they have positive attitudes towards providing asthma PC. Pharmacists have crucial role in asthma care with leveraging their expertise, patient interactions, and ability to referral capabilities.